Dampak Positif dan Negatif Pemanfaatan Teknologi Multimedia dalam Dunia Pendidikan: Tinjauan Literatur - Andika Faza Setiawan; Isnaeni Kholifatun; Riskha Syofiyana; Muhammad Rikzam Kamal (CV. Cendekiawan Muda Sriwijaya, 2025)
This study is a literature review aimed at comprehensively analyzing the positive and negative impacts of multimedia technology utilization in education. Data was obtained from 15 scientific works, including international journals, accredited and non-accredited national journals, proceedings, and relevant theses. The findings indicate that the use of interactive multimedia contributes positively to enhancing motivation, learning outcomes, creativity, student engagement, and supporting teacher professionalism. However, there are also negative impacts such as excessive cognitive load, concentration disruptions, and the potential for digital addiction. The main challenges identified include infrastructure limitations, low digital literacy, and insufficient teacher training. Therefore, the implementation of multimedia in education requires well-developed strategies and robust systems to achieve optimal and sustainable outcomes.